2009
DOI: 10.5194/nhess-9-1471-2009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the summit lakes of Ambae volcano and their potential for generating lahars

Abstract: Abstract. Volcanic eruptions through crater lakes often generate lahars, causing loss of life and property. On Ambae volcano, recent eruptive activities have rather tended to reduce the water volume in the crater lake (Lake Voui), in turn, reducing the chances for outburst floods. Lake Voui occupies a central position in the summit caldera and is well enclosed by the caldera relief. Eruptions with significantly higher magnitude than that of 1995 and 2005 are required for an outburst. A more probable scenario f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…8 reveal substantial differences in SO 2 flux from the six studied volcanoes, which primarily reflect their levels of activity. The highest SO 2 emission rate (33 Gg day − 1 ) was recorded at Ambrym during a three-month pulse of strong lava lake degassing in 2005 (Bani et al, 2009a), while the smallest emission rate (9 Mg day − 1 ) is from fumarolic activity on Vanua Lava. Ambrym is a predominantly basaltic volcano, with persistent lava lake activity and a prodigious plume emission that makes it by far the strongest source of SO 2 in Vanuatu ( [Allard et al, 2009] and [Bani et al, 2009a] ).…”
Section: Ultraviolet Spectrscopic Measurementsmentioning
confidence: 95%
See 3 more Smart Citations
“…8 reveal substantial differences in SO 2 flux from the six studied volcanoes, which primarily reflect their levels of activity. The highest SO 2 emission rate (33 Gg day − 1 ) was recorded at Ambrym during a three-month pulse of strong lava lake degassing in 2005 (Bani et al, 2009a), while the smallest emission rate (9 Mg day − 1 ) is from fumarolic activity on Vanua Lava. Ambrym is a predominantly basaltic volcano, with persistent lava lake activity and a prodigious plume emission that makes it by far the strongest source of SO 2 in Vanuatu ( [Allard et al, 2009] and [Bani et al, 2009a] ).…”
Section: Ultraviolet Spectrscopic Measurementsmentioning
confidence: 95%
“…A total of 55 days of fieldwork were necessary to assemble this dataset. We integrate here data that have been presented in our previous studies ( [ Bani and Lardy, 2007] , [Bani et al, 2009a] and [Bani et al, 2009b] ) but more than two-thirds of the flux measurements reported here are new (Table 1). Measurement frequency has been strongly determined by access conditions, available funding and serendipity.…”
Section: Ultraviolet Spectrscopic Measurementsmentioning
confidence: 98%
See 2 more Smart Citations
“…Maar lakes basin fi lls are frequently considered as key environments for paleoclimate reconstructions (Sifeddine et al 1996 ;Thouveny et al 1994 ;Oldfi eld 1996 ;Ariztegui et al 2001 ;Brauer et al 1999 ;Caballero et al 2006 ;Augustinus et al 2012 ;Zolitschka et al 2013 ) but little is known about the triggering factors of gravity reworking phenomena and related natural hazards (Giresse et al 1991 ;Truze and Kelts 1993 ;Bacon et al 2002 ;Bani et al 2009 ;Zolitschka et al 2013 ). There is particularly a need to improve our understanding of subaquatic slope stabilities, since maar basins are frequently characterized by steep slopes, a conical morphology and no large infl ows (Chap.…”
Section: Introductionmentioning
confidence: 99%